Video documental sibre el ciclista y artista urbano de las calles de Quito Sebastián Muñoz (+) - Masache Heredia, Javier Andrés (2015)
This work, as well as the documentary accompanying product is intended to pay tribute to the life of a street artist and cyclist in Quito on a personal level; in the sociocultural level is also intended to show some irregularities in both public policy and the culture of the inhabitants of the city in the fields of mobility and road traffic as a topical issue. Framed in communicative action and the visual impact of a documentary video. Sebastián Muñoz is on whom turns the subject and from where will derive political, social, cultural and communication issues deepen a topic of general interest that can be generated subsequently to encourage a much more pedestrian friendly consciousness, to cyclist and the drivers of vehicles, both public and private. It has taken the vision of Sebastian's family, friends, fellow artists and colleagues about his life and his unfortunate death on March 22, 2013 when, in early morning, was hit precisely while riding his bike by a car that was driving over the speed limit. In Ecuador new cultural movements such as cyclists have appeared, which beyond a hobby, has become a way of life with cultural and political demonstrations. Moreover it is a product video set to serve as pilot for many other student research projects and staging within the genre of documentary on the career of Social Communication of the Universidad Politécnica Salesiana.